H-Mode Power Threshold Studies on MAST † - Andrew,Y; Bähner,JP; Battle,R; Jirman,T (Plasma, 2019)
Analysis of the L–H and H–L transition power thresholds (Pth) and pedestal parameters are presented for the mega ampere spherical tokamak (MAST). The dependencies of Pth on the average, core plasma electron density, X-point height, and plasma current are described. Increasing X-point distance from the divertor floor over 10–12 cm is found to increase Pth by a factor of three, while X-point heights greater than this have no further influence. The X-point height dependence of Pth is also observed to be sensitive to the plasma current. An Ip decrease from 0.77 MA to 0.65 MA, is observed to lower Pth by a factor of three across the X-point height scan and increases the maximum X-point height at which Pth stops increasing by 3 cm. Finally, a comparison of the experimental results with the predictions by the finite beta drift wave model is made, which provides a reasonable condition for the transition into and out of the H-mode.